United States naval aviation, 1919-1941 aircraft, airships and ships between the wars - Johnson, E.R (McFarland & Company, 2011)
Within six months of Japan's devastating attack on Pearl Harbor, the U.S. navy had slowed the empire's military advance in the Pacific so much that the United States could return to its original "Germany First" strategy. That the navy was able to accomplish this feat with only six fleet aircraft carriers and a little more than 1,000 combat aircraft was the culmination of more than two decades of determined preparation. This thorough study summarizes the factors critical in shaping naval aviation after World War I, including naval treaties, fleet tactics, government programs, leadership and organization, and the emergence of Marine Corps and Coast Guard aviation. Detailed technical drawings of individual aircrafts, airships, and ship development illustrate the 22-year process of trial and error that ultimately enabled U.S. naval aviation to prevail during the early months of World War II.